Lineamientos para una propuesta de política pública de recuperación productiva: Manabí 2016 (Tema Central) - Lanas Medina, Elisa Verónica (2018)
The 2016 earthquake, with an epicenter in Manabí, created the opportunity to analyze if Ecuador has risk management public policies, analyze the institutional framework of the mechanisms to respond during and after a disaster and, if the post-disaster management includes policies to reactivate productive activities. It is a mixed research, with exploratory and descriptive scope and the aim of proposing guidelines for public policy in post-disaster management with alternative production processes, based on solidarity economy, as a recovery mechanisms. The most significant finding is that Ecuador does not have adequate public policies for risk management, the institutions are weak and the community is not resilient; also, it was identified that it is necessary to make a diagnosis of the reality of the territory to outline the guidelines to propose the public policy of productive recovery through associative and solidarity processes.